MODEL PENDAMPINGAN PEMBIAYAAN MIKRO PADA MAHASISWA BERBASIS ENTREPRENEURSHIP - Aisyah, Esy Nur (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Increasing entrepreneurial spirit requires new breakthroughs. The aim is to increase entrepreneurial spirit to students in business establishments. The development of a microfinance mentoring model based on entrepreneurship can educate students to participate in reducing the number of poverty and unemployment. The purpose of this study was to design a microfinance mentoring model for entrepreneurship-based students at the El Dinar Finance House Laboratory. Financing assistance model uses matching programs to courses related to finance and business, for example, the business plan courses that are followed by students of entrepreneurial concentration and financing analysis courses followed by students of financial concentration. Lecturers in each courses coordinate with the laboratory team regarding real-time mentoring and evaluation of student practice. The assistance carried out by El-Dinar Finance House is 1) Monitor the mutation of the customer's bank account, 2) Monitor the repayment of installments, 3) visit the customer's business location to directly monitor the business operations and business development (financial statements), 4) monitor against the development of similar businesses through mass media or other media.Â